The role of mitochondria in neurodegenerative diseases: mitochondria as a therapeutic target in Alzheimer’s disease - Reddy, P. Hemachandra (2009)
Mitochondria are cytoplasmic organelles responsible for life and death. Extensive evidence from animal and clinical studies suggests that mitochondria play a critical role in aging, cancer, diabetes and neurodegenerative diseases, such as Alzheimer's disease, Parkinson's disease, and Huntington's disease. Several lines of research suggest that mitochondrial oxidative damage is an important cellular change in most late-onset neurodegenerative diseases. Further, emerging evidence suggests that structural changes in mitochondria, including increased mitochondrial fragmentation and decreased mitochondrial fusion, are critical factors associated with mitochondrial dysfunction and cell death in aging and age-related diseases. In addition, epigenetic factors and lifestyle activities may contribute to selective disease susceptibility for each of these diseases. This paper discusses research that has elucidated features of mitochondria that are associated with cellular dysfunction in aging and neurodegenerative diseases. This paper also discusses mitochondrial abnormalities and potential mitochondrial therapeutics in AD.